Correlations Between Symptoms, Nasal Endoscopy Computed Tomography and Surgical Findings in Patients with Chronic Rhinosinusitis - Pokharel, M; Karki, S; Shrestha, BL; Shrestha, I; Amatya, RCM (Kathmandu University Medical Journal, 2015)
Background Although Chronic rhinosinusitis (CRS) is increasing in prevalence and incidence, its diagnosis and treatment still pose a challenge. The Task Force on rhinosinusitis (TFR) advocates the use of symptom based criteria. However, many otorhinolaryngologists depend on diagnostic nasal endoscopy and computed tomography(CT) of paranasal sinuses for diagnosis of CRS. Computed tomography has been extensively relied upon in confirming the presence of CRS, in assessing severity of disease, surgical planning and management decisions. Despite its widespread use, several studies have failed to correlate findings on CT with symptom severity. Objective To determine the correlations between symptoms described at presentation, radiological findings, endoscopy and extensiveness of surgery. Methods Longitudinal, prospective, analytical study conducted from August 2011 to August 2012 among 87 patients diagnosed as CRS according to the TFR criteria. Symptom, endoscopic, radiological and surgical scoring was done by using Lund and Mackay staging system. Pearson correlation coefficients between scores for symptoms, endoscopy, sinus CT and surgery was determined. Results When overall symptom score was correlated with radiological score and endoscopy score, it was found to be statistically significant (p=